Text, interpretability and interpretation: limits and scope - Finol, José Enrique (2017)
This investigation briefly revises some of the theories regarding interpretation and stipulates which are the limits and reaches which define it. It parts from Semiotic proposals (Eco, Greimas), Hermeneutics (Ricoeur) and the Critical Discourse Analysis (van Dijk). The concepts of “interpretability” and “fiduciary contract” are proposed, and recent analytical experiences are revised to demonstrate that there are no such things as limitless interpretations, and to point out some heuristic tools that allow for the development of viable interpretations.